2020
DOI: 10.5812/ijpbs.84188
|View full text |Cite
|
Sign up to set email alerts
|

Relationship Between Oxidative Stress Concentration and Postpartum Depression: A Cohort Study

Abstract: Background: Postpartum depression is a mood disorder that has harmful effects on infants and family relationships. However, its low diagnostic rate (50%) limits the proper treatment of women suffering from this disorder. The identification of women who are at risk can be useful. Oxidative stress may be a risk factor for depression. Oxidative stress occurs when the production of reactive species exceeds the capacity of cellular antioxidant defenses to remove these toxic species. However, little is known about t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 23 publications
1
4
0
1
Order By: Relevance
“…Consistent with our findings, many studies have found that lower levels of antioxidants and higher levels of oxidative stress biomarkers, such as MDA, play a role in the development of depression [39][40][41]. In the meantime, there is some research indicating that there were no significant differences in MDA levels between the depressed and non-depressed groups [42,43]. In addition, many studies, as well as our results, reported that there was a significant difference in antioxidant enzymes between patients with major depression, including PPD, and nondepressed participants [44,45].…”
Section: Discussionsupporting
confidence: 91%
“…Consistent with our findings, many studies have found that lower levels of antioxidants and higher levels of oxidative stress biomarkers, such as MDA, play a role in the development of depression [39][40][41]. In the meantime, there is some research indicating that there were no significant differences in MDA levels between the depressed and non-depressed groups [42,43]. In addition, many studies, as well as our results, reported that there was a significant difference in antioxidant enzymes between patients with major depression, including PPD, and nondepressed participants [44,45].…”
Section: Discussionsupporting
confidence: 91%
“…So far, only a handful of studies have evaluated the role played by antioxidants in depressive symptoms or depression (Beydoun et al, 2013). A relationship was reported between the serum total antioxidant capacity and postpartum depression (Alamolhoda et al, 2020). MDA is the main reflecting factor during PPD.…”
Section: Discussionmentioning
confidence: 99%
“…High expression of proinflammatory cytokines (such as interleukin (IL)-1β, TNF-α, and IL-6) has been observed in inflammation models of depression in rodents. Furthermore, the results of a recent prospective cohort study on the relationship between oxidative stress and postpartum depression showed a significant inverse correlation between serum total antioxidant capacity and EPDS scores [ 12 ]. A recent meta-analysis of studies that reported immune marker levels in the peripheral blood of patients with depression and matched the healthy controls revealed significant elevations in the levels of several proinflammatory cytokines and C-reactive protein in patients with depression [ 76 ].…”
Section: Biological Mechanisms That Might Underlie Selenium’s Effects...mentioning
confidence: 99%
“…Pathophysiological mechanisms underlying postnatal depression are diverse. The roles of neuroendocrine alterations, disruptions in neurotransmission, circuit dysfunction, neuroinflammatory processes, and oxidative stress over the course of gestation, as well as genetic and epigenetic factors, have been discussed [ 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%